2021
DOI: 10.1093/gbe/evab020
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics Suggests a Taxonomic Revision of the Staphylococcus cohnii Species Complex

Abstract: Staphylococcus cohnii (SC), a coagulase-negative bacterium, was first isolated in 1975 from human skin. Early phenotypic analyses led to the delineation of two subspecies (subsp.), Staphylococcus cohnii subsp. cohnii (SCC) and Staphylococcus cohnii subsp. urealyticus (SCU). SCC was considered to be specific to humans whereas SCU apparently demonstrated a wider host range, from lower primates to humans. The type strains ATCC 29974 and ATCC 49330 have been designated for SCC and SCU, respectively. Comparative an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…With the rapid development of sequencing techniques, the genomes of diverse bacterial strains have been sequenced. This advancement promoted research on comparative genomics, which helped illustrate the relationships between genotypes and phenotypes ( Wang et al, 2018 ), thereby addressing the effects of isolation source on the genetic variations ( Mao et al, 2021 ), revealing horizontal gene transfer ( Singh et al, 2021 ), and performing taxonomic revision ( Lavecchia et al, 2021 ). As the importance of Weissella species has been recognized, attempts have been made to explore their evolutionary relationship and genomic characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of sequencing techniques, the genomes of diverse bacterial strains have been sequenced. This advancement promoted research on comparative genomics, which helped illustrate the relationships between genotypes and phenotypes ( Wang et al, 2018 ), thereby addressing the effects of isolation source on the genetic variations ( Mao et al, 2021 ), revealing horizontal gene transfer ( Singh et al, 2021 ), and performing taxonomic revision ( Lavecchia et al, 2021 ). As the importance of Weissella species has been recognized, attempts have been made to explore their evolutionary relationship and genomic characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Staphylococcus pettenkoferi clusters within the Auricularis species group, rather than the Saprophyticus species group as previously reported ( Lamers et al 2012 ). The use of genomic analysis to resolve complex or conflicting taxonomic assignments in Staphylococcus has been previously demonstrated ( Madhaiyan et al 2020 ; Lavecchia et al 2021 ), and our results will further inform future classification efforts in this genus.…”
Section: Resultsmentioning
confidence: 52%
“…In S. cohnii , however, sxs A is not part of the core genome, as it was only identified in a small group of strains, all isolated from a dairy environment/bovine mastitis infection (either SNUC strains originating from Canada or SC strains, originating from Germany). When considering a recent taxonomic revision published by Lavecchia et al (2021), which revealed three phylogenetically distinct lines within S. cohnii , sxs A‐positive isolates all correspond to group A2, a group proposed by the authors to be reclassified to Staphylococcus cohnii subsp. barensis .…”
Section: Resultsmentioning
confidence: 99%